2004
DOI: 10.1007/s00436-004-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between fish reproductive cycle and the dynamics of metazoan parasite infection

Abstract: The parasite fauna of the stone loach (Barbatula barbatula) was investigated monthly from May to December 2001. Four parasite species were recorded: Gyrodactylus spp. (Monogenea), Tylodelphys clavata (Digenea), Proteocephalus sagittus (Cestoda), and Raphidascaris acus (Nematoda). The changes in the seasonal dynamics of parasite infection were investigated throughout the 8 months. The potential effect of the reproductive investment of the host, measured by gonad mass and gonado-somatic index (GSI), on the paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 25 publications
4
44
0
2
Order By: Relevance
“…This implies seasonal development of the tapeworm and infection with plerocercoids before summer. Similar results have been observed for the congeneric tapeworm Proteocephalus sagittus (Jarkovský et al, 2004;Š imková et al, 2005). Based on the present results, it is therefore presumed that the yellowhead catfish became infected with G. pseudobagri through digestion of copepods in the spring.…”
Section: Discussionsupporting
confidence: 91%
“…This implies seasonal development of the tapeworm and infection with plerocercoids before summer. Similar results have been observed for the congeneric tapeworm Proteocephalus sagittus (Jarkovský et al, 2004;Š imková et al, 2005). Based on the present results, it is therefore presumed that the yellowhead catfish became infected with G. pseudobagri through digestion of copepods in the spring.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that the host sex had no statistically significant effect on the degree of infection in most studied species, except in hake and whiting, where females were more infected, probably related to the faster growth of females in these demersal species (54). Šimková et al (55) related the greater infection of the gill monogenean parasites in female fish to the greater investment of females in reproduction, which produces larger gametes than in males. The authors observed a positive correlation between parasite infection and gonad weight and the gonadosomatic index, although this does not fully explain the higher affinity of the parasite for female hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Simková et al (2005) encontraron un incremento de la parasitosis con el aumento del IGS con la abundancia de monogeneos, cestoda y digeneos en el pez Barbatula barbatula (Linnaeus, 1758) (Balitoridae), indicando que los peces son más susceptibles a la infección parasitaria en los periodos de mayor gasto reproductivo. Los índices de diversidad alfa (H I y J I ) de la parasitofauna de I. conceptionis mostraron valores relativamente altos y los índi-ces de dominancia (λ y I B-P ) tuvieron valores bajos.…”
Section: Discussionunclassified